Aplikasi Inventory Barang Berbasis Website untuk Divisi General Affair dalam Pendataan Barang PT. GED Lintas Indonesia - Saputra, Muhammad Hadi; Ike Meilani, Yayuk; Jhonsen Syaftriandi, Muhammad; Effendi, Yanti (MDP Student Conference, 2024)
The data collection process still uses a simple method, namely using a paper form to collect stock taking data for all items and using a stock card to collect data on goods. This research aims to create a web-based inventory application that can reduce the risk of errors compared to a manual recording system. The method used is the RAD method. This method is an information system development method that is considered to emphasize short development cycles, so it is considered appropriate to use in developing this system. RAD uses an iterative method in developing a system. The stages that support this method are define the requirements, prototype, receive feedback, and finalize software. The results of this research are a web-based goods inventory application interface that is used to collect goods data and create stock taking reports quickly and accurately.